2003
DOI: 10.1111/j.1534-6935.2003.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation profiles in 27 horses with large colon volvulus

Abstract: Objective: The objective of this study was to evaluate coagulation profiles in horses with surgical treatment of large colon volvulus (LCV), and determine if an association exists between hemostatic dysfunction and outcome. Design: Prospective clinical investigation from February to December 2000. Setting: Large animal intensive care unit in a veterinary teaching hospital. Interventions: Blood was collected from horses intra-operatively, 24, and 48 hours following surgical treatment for LCV. Measurements: Coag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
126
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(139 citation statements)
references
References 27 publications
9
126
2
1
Order By: Relevance
“…Mean PLT and MPV gradually decreased due to surgery for intestinal displacement. Various authors have indicated that after surgical intervention thrombocytopenia is more likely to occur than after conservative treatment (Chang 1996;Dallap et al 2003;Yaguchi et al 2004). Postoperative reduction of platelet counts may be due to platelet activation and subsequent consumption in the process of clot formation, sequestration in the spleen or adhesion to endothelial surfaces, as well as destruction and exhaustion of thrombopoiesis (Levi et al 1997;Salat et al 1999;Nunez et al 2001;Kimberley et al 2004;Levi and Opal 2006;Alsaad and Nori 2009;Levi et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mean PLT and MPV gradually decreased due to surgery for intestinal displacement. Various authors have indicated that after surgical intervention thrombocytopenia is more likely to occur than after conservative treatment (Chang 1996;Dallap et al 2003;Yaguchi et al 2004). Postoperative reduction of platelet counts may be due to platelet activation and subsequent consumption in the process of clot formation, sequestration in the spleen or adhesion to endothelial surfaces, as well as destruction and exhaustion of thrombopoiesis (Levi et al 1997;Salat et al 1999;Nunez et al 2001;Kimberley et al 2004;Levi and Opal 2006;Alsaad and Nori 2009;Levi et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Acute colic causes such as large colon volvulus can induce changes in the coagulation system (Dallap et al 2003). These changes are secondary to the haemodynamic and functional disorders of the gastrointestinal tract and are also a consequence of an inflammatory process (Levi et al 1997;Dallap et al 2003;Levi and Opal 2006;Dallap Schaer and Epstein 2009;Levi et al 2011).…”
mentioning
confidence: 99%
See 3 more Smart Citations